2006
DOI: 10.1158/0008-5472.can-06-1346
|View full text |Cite
|
Sign up to set email alerts
|

Role of SPA-1 in Phenotypes of Chronic Myelogenous Leukemia Induced by BCR-ABL–Expressing Hematopoietic Progenitors in a Mouse Model

Abstract: SPA-1 is a negative regulator of Rap1 signal in hematopoietic cells, and SPA-1-deficient mice develop myeloproliferative disorders (MPD) of long latency. In the present study, we showed that the MPDs in SPA-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Previous studies showed that the majority of the Sipa1 2/2 mice and 15% Sipa1 1/2 mice developed CML-like MPN. 15,25 We here observed MDS-like MPN mainly in the aged Sipa1 2/2 female mice. This discrepancy in the observed disease phenotype might be due to different genetic background of the mice.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies showed that the majority of the Sipa1 2/2 mice and 15% Sipa1 1/2 mice developed CML-like MPN. 15,25 We here observed MDS-like MPN mainly in the aged Sipa1 2/2 female mice. This discrepancy in the observed disease phenotype might be due to different genetic background of the mice.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, AQP2 trafficking to the apical membrane is impaired in the collecting duct principal cells of SPA-1-deficient mice [68]. SPA-1-deficient mice show marked bilateral hydronephrosis due to polyuria [43,68].…”
Section: Exocytosismentioning
confidence: 99%
“…7 We also reported that human bcr-abl fusion gene product (Bcr-Abl) was a potent Rap1 activator, 8 and that Bcr-Abl ϩ SPA-1 Ϫ/Ϫ HPCs showed aggravated chronic myelogenous leukemia phenotypes compared with Bcr-Abl ϩ wild-type HPCs in a mouse model, including prolonged survival of leukemic progenitors and rapid blast crisis in vivo. 9 Thus, proto-oncogenes capable of activating Rap1 signal may be potential collaborative factors for leukemia in SPA-1 deficiency.…”
Section: Introductionmentioning
confidence: 99%